¿Quién es el genio de Kant? (2021)
The nature of the Kantian genius, one of the most disturbing figures in the aesthetics of the philosopher of Königsberg, is discussed, conjecturing about the possible role of freedom of the imagination in the genius’ task of “giving rule to art”. The darkness of the philosopher is postulated to explain the origin of the genius, darkness that would be explained by the permanent tension that crosses all the critique of aesthetic judgement between genius and taste, or if you like, between freedom and academia.